2017
DOI: 10.1017/pasa.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Asymmetry Between Clockwise and Counterclockwise Spiral Galaxies in SDSS

Abstract: While galaxies with clockwise and counterclockwise handedness are visually different, they are expected to be symmetric in all of their other characteristics. Previous experiments using both manual analysis and machine vision have shown that the handedness of Sloan Digital Sky Survey (SDSS) galaxies can be predicted with accuracy significantly higher than mere chance using its photometric data alone, showing that the photometric pipeline of SDSS is sensitive to the handedness of the galaxy. However, some of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(99 citation statements)
references
References 32 publications
2
97
0
Order By: Relevance
“…Mean, standard error of the mean, and the one-tail P value of the differences between the magnitude of clockwise galaxies and counterclockwise galaxies in COSMOS such that the 5% highest values and the 5% lowest values were removed. The SDSS data were taken from previous work (Shamir 2017c). The number of SDSS galaxies in that field is 5447 counterclockwise galaxies and 5774 clockwise galaxies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean, standard error of the mean, and the one-tail P value of the differences between the magnitude of clockwise galaxies and counterclockwise galaxies in COSMOS such that the 5% highest values and the 5% lowest values were removed. The SDSS data were taken from previous work (Shamir 2017c). The number of SDSS galaxies in that field is 5447 counterclockwise galaxies and 5774 clockwise galaxies.…”
Section: Resultsmentioning
confidence: 99%
“…More recent experiments with a much larger dataset (Kuminski & Shamir 2016;Paul et al 2018) of ∼ 1.62 • 10 5 galaxies showed a clear statistically significant difference (P< 10 −5 ) between the magnitude of galaxies with clockwise spin patterns and galaxies with counterclockwise spin patterns (Shamir 2017c). The experiments also showed that the photometric differences changed with the direction of observation (Shamir 2017c). These observations are consistent across SDSS and Pan-STARRS, both showing the same profile of the asymmetry (Shamir 2017b).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The dataset that was used in this study is a dataset of SDSS galaxies designed for experiments related to photometry of galaxies [21]. Here the dataset is tested for the identification of non-random distribution of galaxy spin directions, and for that purpose photometric objects that are part of the same galaxies were removed.…”
Section: Discussionmentioning
confidence: 99%
“…Since such subtle biases are often difficult to identify, the analysis method needs to be a symmetric method. More information about Ganalyzer is available in [19], and the process of the galaxy annotation is described in [21,22].…”
Section: Datamentioning
confidence: 99%